Respuesta :

Answer:

This system can be solved for x by elimination.

[tex]6x - 3y = 15\\ x + 3y = -8\\\\7x = 7\\\\x = 1[/tex]

Now, with what we found for x, we plug it back into one of the equations to solve for y. I chose the second one.

[tex]1 + 3y = -8\\\\3y = -9\\\\y = -3[/tex]

Now, we have our solution.

[tex](1, -3)[/tex]

Answer:

(1,-3)

Step-by-step explanation:

6x-3y=15

substitute x with 1 and y with -3

6(1)-3(-3)=15

6+9=15 so that's true

x+3y=-8

again substitute x with 1 and y with -3

(1)+3(-3)= -8

1-9=-8

-8=-8 and that's true

hope i helped

ACCESS MORE